MENINGKATKAN KEMAMPUAN MENGENAL NILAI MATA UANG BAGI ANAK TUNAGRAHITA RINGAN KELAS VII DI SLB NEGERI TANJUNGPINANG - Sugino - Sugino (Jurnal Penelitian Pendidikan Khusus, 2013)
The present Currency Value Through Role Playing Method for Children Tunagrahita Kelas.Penelitian Light is motivated by problems in the field, mild mental retardation children of class VII in SLB Tanjungpinang State, amounting to 8 people. Children do not know the value unag. for everyday life, the ability to use Currency Value Through Role Playing Method for Children Tunagrahita SLB Light District VII Class Tanjungpinang.Metodologi research is action research (Classroom Action Research). The research process was conducted in two cycles, namely cycle 1 and cycle II. Implementation of cycle 1 cycle begins with the buying and selling activities were demonstrated in class by playing a role which consisted of three rounds of the preparation phase, the implementation phase and the follow-up phase. The results of the first cycle is categorized been able to, followed the second cycle. In the second cycle of the efforts the ability to use the value of the currency through role play method with the method of playing the role of a money exchange activities, shopping dikantin manner refunds.